1974
DOI: 10.1111/j.1365-3180.1974.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of manual and chemical defoliation on the growth and carbohydrate reserves of Panicum repens (L.) Beauv.

Abstract: Summary: Résumé: Zusammenfassung In pot experiments on Panicum repens manual and chemical defoliation at intervals of 2–6 weeks decreased the growth of shoots, roots and new rhizomes and reduced the carbohydrate reserves. The most frequent manual defoliation did not completely suppress growth even when continued for 9 months. The plants were killed, however, by application of paraquat at doses of 0–14‐0′56 kg/ha every 2 weeks for a period of 3 months. It is suggested that repeated mechanical defoliation may he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…1988). Problems with flood control, navigation, recreation and irrigation are encountered when torpedograss becomes established due to its ability to invade diverse ecosystems (Manipura & Simaratne, 1974;Fleming, Palmertree & Houston, 1978;Baird et al. 1983a;Baird et al, 1983b;Wilcut et ai, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1988). Problems with flood control, navigation, recreation and irrigation are encountered when torpedograss becomes established due to its ability to invade diverse ecosystems (Manipura & Simaratne, 1974;Fleming, Palmertree & Houston, 1978;Baird et al. 1983a;Baird et al, 1983b;Wilcut et ai, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation before seven days after application reduced glyphosate efficacy indicating that translocation to the rhizomes of lorpedograss took seven days or longer. Manipura & Simaratne (1974) showed that mechanical defoliation every two weeks for nine months did not provide complete control of torpedograss. but paraquat treatments every two weeks for three months did.…”
Section: Introductionmentioning
confidence: 99%
“…Poor torpedograss seed viability may indicate dissemination occurs primarily through vegetative propagation of rhizome‐contaminated soils (22,28). Torpedograss’ regenerates from rhizome fragments high in carbohydrate reserves (19,28). The rapid growth of torpedograss is capable of producing dense rhizome systems within a few months under favorable growing conditions (7).…”
Section: Torpedograss Infestation Of Warm‐season Turfgrassesmentioning
confidence: 99%
“…A dificuldade no controle de Panicum repens está relacionada com a grande capacidade e rapidez com que as plantas se recuperam, principalmente em função das reservas de carboidratos nos rizomas (Manipura & Somaratne, 1972 Médias seguidas de mesma letra, na coluna, não diferem estatisticamente entre si pelo teste t (P>0,05); ** valor significativo pelo teste F a (P>0,01). 1/ At = Aterbane 0,5% v/v; 2/ Sil = Silwet 0,1 % v/v; e 3/ aplicação seqüencial do herbicida diquat.…”
Section: Controle Químico De Panicum Repens E Paspalum Repensunclassified